Blowup of Solutions to a Damped Euler Equation with Homogeneous Three-Point Boundary Condition - Obi-Okoye, Ikechukwu; Sarria, Alejandro (The PUMP Journal of Undergraduate Research, 2022)
It is known that solutions to the inviscid Proudman-Johnson equation subject to a homogeneous three-point boundary condition can develop singularities in finite time. Given the regularizing effect that damping can have, in this paper we consider the possibility of finite-time singularity formation in solutions of the generalized inviscid Proudman-Johnson equation with damping subject to the same homogeneous three-point boundary condition. In particular, we will derive criteria the initial condition must satisfy in order for solutions to blowup in finite time under the effect of a smooth time-dependent damping term.